2001
DOI: 10.1097/00004770-200104000-00008
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Interleukin-6 Expression in Human Dental Pulp Cell Cultures Stimulated with Prevotella intermedia Lipopolysaccharide

Abstract: Interleukin (IL)-6 expression in human dental pulp cell cultures after stimulation with Prevotella intermedia lipopolysaccharide (LPS) was investigated by Northern blot analysis, enzyme immunoassay, and bioassay. The IL-6 mRNA expression began to increase after 1 hr and continued after up to 8 hr of exposure on stimulation with 10 microg/ml of P. intermedia LPS. The bioactivity was dose-dependent on the concentration of P. intermedia LPS (0 to 100 microg/ml). The IL-6 mRNA expression was inhibited by actinomys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
45
0
2

Year Published

2002
2002
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(48 citation statements)
references
References 17 publications
1
45
0
2
Order By: Relevance
“…In addition, studies have shown that IL-1␤ and TNF-␣ up-regulate the matrix metalloproteinase and tissue type plasminogen activator (11,12). IL-6 and IL-8 were induced by lipopolysaccharide in HDP cells (13,14). These findings highlight the significance of proinflammatory cytokines in pulpal injury.…”
mentioning
confidence: 79%
“…In addition, studies have shown that IL-1␤ and TNF-␣ up-regulate the matrix metalloproteinase and tissue type plasminogen activator (11,12). IL-6 and IL-8 were induced by lipopolysaccharide in HDP cells (13,14). These findings highlight the significance of proinflammatory cytokines in pulpal injury.…”
mentioning
confidence: 79%
“…Dental pulp cells, especially dental pulp fibroblasts, are known to produce various inflammatory mediators, such as IL-8, IL-6 and vascular endothelial growth factor (VEGF), in response to the components of caries-related bacteria, prior to the discovery and establishment of the innate immune system feature that PRRs including TLRs recognize various PAMPs [29,31,32,58]. TLR2, TLR3, TLR4 and TLR5 expressions have been determined in dental pulp fibroblasts and their specific agonists can induce TLR-mediated inflammatory signals [54,55,59,60], although immunohistological detection of TLRs was not clear in the fibroblasts of dental pulp tissues [49,52].…”
Section: Dental Pulp Cellsmentioning
confidence: 99%
“…With the development of exposure to bacterial components, partial destruction of the odontoblast layer along with severe damage or death of odontoblasts can be observed, and the underlying dental pulp cells including fibroblasts and undifferentiated mesenchymal or stem cells in the cell-rich zone are activated to participate in the host response and initiate reparative dentin formation [26][27][28]. Thus, the dental pulp cells, a major cell type in the dental pulp, play a crucial role in maintaining the structural integrity of connective tissues, and they also have capacity to produce pro-inflammatory cytokines and express adhesion molecules in response to pathogen-associated molecular patterns (PAMPs), which are structures expressed by microorganisms [29][30][31][32][33][34]. Generally, the initial sensing of microbial pathogens is mediated by pattern recognition receptors (PRRs) for PAMPs.…”
Section: Introductionmentioning
confidence: 99%
“…Notably, IL-1 and TNF-a play important roles in immune responses to infection (14). The results of recent studies suggest that LPS induces IL-1, TNF-a, IL-6, and IL-8 in HDPCs (15,16). One host defense mechanism that involves activation of an innate immune response after exposure to the external environment is the production of defensin.…”
mentioning
confidence: 99%